Fingerprint Minutiae Identification Using RLC Method - Kanagalakshmi, K (International Journal of Computer Sciences and Engineering, 2025)
This paper is aimed to design a scheme to mark and extract minutiae of fingerprint using Run-length Coding technique. Minutiae extraction takes vital role in fingerprint based authentication and identifications systems. The scheme comprises of binarization, thinning, minutia marking and extraction. The scheme is tested using the FVC database and real time fingerprint datasets. The Experimental results are presented